2020
DOI: 10.1016/j.ijrobp.2020.07.1814
|View full text |Cite
|
Sign up to set email alerts
|

ALBI Grade vs. Child-Pugh (CP) Score For Stratification Of Survival And Liver Function Decline In Patients With Hepatocellular Carcinoma (HCC) Treated With Radiotherapy (RT)

Abstract: experiencing complete resolution; median time to improvement was 50 days (range 25-117 days). MF persisted in 13/27 (48%). MF resolved in 1/ 3 (33.3%) evaluable patients with chronic fistula. RT did not appear to worsen any MF. Conclusion: In this series, 7.4% of a large cohort of anorectal cancer patients presented with malignant fistula. RT led to improvement or resolution of these in more than half of patients. Persistence of malignant fistula was only observed in patients with refractory disease, and RT di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It can evaluate liver reserve function based on serum albumin and bilirubin levels. In recent years, researchers have found that ALBI grade can predict the prognosis of tumor patients, especially liver cancer patients ( 6 ). In the prognostic evaluation of GC patients, ALBI grade also plays an increasingly important role ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can evaluate liver reserve function based on serum albumin and bilirubin levels. In recent years, researchers have found that ALBI grade can predict the prognosis of tumor patients, especially liver cancer patients ( 6 ). In the prognostic evaluation of GC patients, ALBI grade also plays an increasingly important role ( 7 ).…”
Section: Introductionmentioning
confidence: 99%